2021
DOI: 10.3892/ol.2021.12727
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genomic analysis contrasting primary colorectal cancer and matched liver metastases

Abstract: Recent studies have revealed that colorectal cancer (CRC) displays intratumor genetic heterogeneity, and that the cancer microenvironment plays an important role in the proliferation, invasion and metastasis of CRC. The present study performed genomic analysis on paired primary CRC and synchronous colorectal liver metastasis (CRLM) tissues collected from 22 patients using whole-exome sequencing, cancer gene panels and microarray gene expression profiling. In addition, immunohistochemical analysis was used to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…These genes encode the extracellular matrix proteins LAMA3 and LAMC2 , which have been detected in invasive colon cancer cells and are regulated by transforming growth factor beta 1 and the hepatocyte growth factor produced in the tumor microenvironment [ 97 ]. Another EMT marker/promoter, Spp1 , is highly expressed in liver metastases [ 98 ] and promotes tumor cell migration and invasion [ 99 ]; PLAUR is responsible for the binding and conversion of plasminogen to active plasmin and the subsequent degradation of the extracellular matrix, which in turn promotes invasion and metastasis [ 100 ]. Finally, matrilysin is a matrix metallopeptidase that can degrade extracellular matrix components such as laminins, fibronectin, collagens, and proteoglycans and promote tumor cell invasion and metastatic spread [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…These genes encode the extracellular matrix proteins LAMA3 and LAMC2 , which have been detected in invasive colon cancer cells and are regulated by transforming growth factor beta 1 and the hepatocyte growth factor produced in the tumor microenvironment [ 97 ]. Another EMT marker/promoter, Spp1 , is highly expressed in liver metastases [ 98 ] and promotes tumor cell migration and invasion [ 99 ]; PLAUR is responsible for the binding and conversion of plasminogen to active plasmin and the subsequent degradation of the extracellular matrix, which in turn promotes invasion and metastasis [ 100 ]. Finally, matrilysin is a matrix metallopeptidase that can degrade extracellular matrix components such as laminins, fibronectin, collagens, and proteoglycans and promote tumor cell invasion and metastatic spread [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that in the metastatic setting, molecular features of the primary tumour were less prognostic and that analysis of the metastatic deposit differed and could more powerfully predict clinical outcomes based on three groups: canonical, immune and stromal subtypes. Differential genomic signatures between the primary tumour and the metastatic deposit have been demonstrated by other groups [ 29 ].…”
Section: Colorectal Cancer—personalised Medicine For a Heterogeneous Diseasementioning
confidence: 82%
“…These genes encode the extracellular matrix proteins LAMA3 and LAMC2 , which have been detected in invasive colon cancer cells and are regulated by transforming growth factor beta 1 and hepatocyte growth factor produced in the tumor microenvironment [97]. Another EMT marker/promoter, Spp1 , is highly expressed in liver metastases [98] and promotes tumor cell migration and invasion [99]; PLAUR is responsible for the binding and conversion of plasminogen to active plasmin and subsequent degradation of the extracellular matrix, which in turn promotes invasion and metastasis [100]. Finally, matrilysin is a matrix metallopeptidase that can degrade extracellular matrix components such as laminins, fibronectin, collagens, and proteoglycans and promote tumor cell invasion and metastatic spread [101].…”
Section: Discussionmentioning
confidence: 99%